INFLUENCE OF SOME TECHNOLOGICAL FACTORS OVER VIBRATION SPEED WHEN MILLING WHITE PINE DETAILS ON A UNIVERSAL WOOD SHAPER (Innovation in Woodworking Industry and Engineering design, 2026)
This study presents how some technological factors influence the vibrations of the cutting mechanism in a woodworking shaper. The experiment was carried out at different operating rotation frequencies and with cutting tools of different diameters. During the experiment, scots pine (pinus sylvestris) test samples were milled. Measurements were made at four points in the radial direction. Two of them are located in the upper bearing housing, and the other two are in the lower bearing housing. A universal milling machine with a lower position of the working shaft is used for the experiment. During the research, attention was paid to some technological factors such as cutting speed, feed speed of the processed material which is from 4m.min-1 to 16m.min-1, milling width 12 mm and thickness of removed layer 12 mm. The study is aimed at improving the reliability and efficiency of a wood shaper machine as well as ensuring the accuracy and quality of products.